Money and Prices: A Model of Search and Bargaining - Shouyong Shi (Queen's University, Department of Economics, 1995)
This paper makes commodities divisible and incorporates bargaining into the search-theoretic model of money to determine the purchasing power of money (or price). It is shown that two monetary equilibria always coexist where flat money is universally accepted. The two equilibria differ in price, output, welfare and the velocity of money. Sunspot monetary equilibria exist in which money is universally accepted in all states of the economy. Multiplicity has novel implications on the effectiveness of currency substitution and exchange market intervention.
Keywords: E40; C78; 330